A biomechanical approach to Paralympic cross-country sit-ski racing - Gastaldi, L.; Pastorelli, S.; Frassinelli, S. (Clinical Journal of Sport Medicine, 2012)
Objective: To analyze the biomechanics of the double poling (DP) gesture in cross-country disabled sit-skiers in the field during competition.